VD_FINDINFO Jug / 2011 / 291 vom 6. Mai 2011 - VD Tribunal cantonal (2011)
COAUTEURDROIT PÉNAL, PARTICIPATION À L'INFRACTION, SURSIS À L'EXÉCUTION DE LA PEINE | 140 ch. 4 CP, 40 CP, 47 CP, 50 CP, 51 CP